Inter-administrative agreements Agreements Are a mechanism that replaces the Public tenders? (2013)
Public procurement is the tool used by the state to run the public resources allocated to each entity , which are used for the development of its purpose and public policy , on the principle of transparency as reflected in the projection and approach to the implementation of these resources in a given period . For this we take as support mechanisms and public tenders inter- administrative agreements , which allow us to run the resources to meet the specific need you have and manage an agile and transparent public resources allocated to a particular activity , according to the agenda scheduled and performed at the beginning of each period. To run these agile resources and ensuring that these resources are protected and well managed , it makes use of contractual mechanisms such as the inter-administrative agreements with universities , and we certify that this excellent performance and public resource protection through guarantees and supported in these universities have experience in implementing various contractual objects , allowing the performance takes place in a timely manner , legitimizing rationale for agreements where there is the voluntary agreement for each participant seeks to satisfy mutual support needs